Kajian Lafaz ditinjau dari Indikasi Maknanya: Dalālah al-mafhūm al-Mukhālafa (Ḥaṣr, Ṣifah, Syarṭ, Laqab, Ġāyah, dan ‘Adad) - Muhammad Fitrah Waila Zamzani; Muh Farid Wadjedy; Fatmawati; Abd. Rauf Muhammad (Cv. Kayaswara, Indonesia, 2025)
This study examines the concept of mafhūm al-mukhālafah in the discipline of uṣūl al-fiqh as one of the methods of legal derivation (istinbāṭ al-ḥukm) from the Qur’an and Hadith. Conducted through library research, the data were collected from classical and contemporary works of Islamic jurisprudence, along with supporting academic literature. The findings indicate that mafhūm al-mukhālafah is understood as a meaning derived not directly from the text, but from its opposite implication. Scholars classify mafhūm al-mukhālafah into several types, including mafhūm al-ḥaṣr, al-ṣifah, al-sharṭ, al-ghāyah, al-‘adad, and al-laqab. Each type has its own distinctive rules of application, yet all share the same principle that legal rulings may be derived from implied meanings. This study highlights the significance of mafhūm al-mukhālafah as an important tool of legal reasoning in Islamic law and reflects the dynamic scholarly discourse surrounding its application.